Sensors of non-electric quantities - Tomashevskyi, R. S.; Chmykhova, O. V.; Varshamova, I. S. (National Technical University "Kharkiv Polytechnic Institute", 2023)
The book presents the basics of the theory of measurements of non-electrical physical quantities, features of their processing and transmission for use in automatic control systems. For students of specialty 171 "Electronics".
Keywords: textbook; resistive converters; capacitive sensors; induction sensors; piezoelectric sensors; thermocouples; ultrasonic sensors; gas sensors; chemical sensors